STUDY ANALYTICAL CONTENT OF ECO ENZYMES AND THEIR USE IN VARIOUS FIELDS AS A MEANS OF REDUCING ORGANIC WASTE - Nurul Fajriana; Qurratu Aini (Jurnal Biologi Sains dan Kependidikan, 2023)
Types of organic waste produced by households can be processed and reused if people know how to manage it. However, Types of organic waste produced by households can be processed and reused if people know how to manage it. However, the lack of public awareness and knowledge regarding the use and management of waste has resulted in the waste simply piling up and being thrown away, which can damage the environment. In fact, organic waste can be used as fertilizer, animal feed or ecoenzyme. This research aims to determine the content and benefits of using eco enzymes in various areas of life. The research method used is descriptive research method. The data collection technique uses the library study method/literature review obtained from relevant research journals, articles and books. Ecoenzyme fluid contains several types of biological and chemical compounds, namely: Lipase enzymes, Trypsin, Amylase, Acetic acid, Alcohol, Propionic acid, Alkaloids, Saponins, Flavonoids, Phenol, Zn, Mn, Fe, Ca, Mg, S, B, P , K, N, NO3, CO3, O3. Ecoenzyme fluids are useful in the economic, agricultural, environmental, health, household, food and automotive industries.